SERIOUS GAME : LEARNING DIGITAL FORENSIC ACQUISITION TECHNIQUES TO INCREASE COMMUNITY AWARENESS - Muh. Ditra Pamungkas; Syarif Hidayat; Yudi Prayudi (Informatika, Universitas Jenderal Soedirman, 2022)
One of the common causes of cybercrime is the lack of education and public awareness of cybercrime and digital forensics, such as acquisition techniques. So far, only a few people know in general the digital forensic acquisition technique, because learning about this acquisition technique is difficult to obtain and difficult to understand. This study aims to apply Serious Game as a solution in increasing understanding and at the same time promoting the importance of basic acquisition techniques in the world of digital forensics to the public. The method used in this study is the Design Thinking method, which consists of: Empathize, Define, Ideate, Prototype, and Test. The results obtained in this study are a serious game built using the Unity 3D application. There are several displays produced, including: splash screen, quests/challenges, instructions, simulation of acquisition techniques, selection of evidence, and quizzes. Based on the blackbox testing carried out, it was found that the application had been developed as expected.